Extent of Awareness Regarding Natural Resource Management Among Rural Women in Shahdol District of M.P. (Indian Journal of Extension Education, 2016)
A research on awareness of rural women was conducted during 2011 - 2012 to know their extent of awareness regarding Natural Resource Management. Six villages of Shahdol district of Madhya Pradesh province were selected as study area. A sum of 120 women was selected as respondents using equal proportion method. The data was collected through structured, pretested interview schedule. The study confirms that most of the respondents had medium level of knowledge regarding ITK of Natural Resource Management and high extent of awareness regarding management of natural resources . Education, social participation, type of family, land holding, mass media exposure, attitude towards natural resource management were found to have significant association with extent of awareness regarding natural resource management at 0.005 level of significance whereas ITK regarding natural resource management was found to have significant association at 0.01 level of significane. They should be motivated to practice and participate more in such activities.